System Test Approach for Complex Software Systems. Issue 2 (6th August 2021) - Mirchandani, Chandru
ABSTRACT: There is a need to develop a system approach to develop an adaptive model (Mirchandani 2010) by which the changes in the testing and upgrade or 'problem‐fix' processes for complex software are monitored in real‐time and incorporated in the development of reliability models for software systems. As system engineers it is our goal to develop, elegant designs that will implement the required capability, i.e., produce the intended result (IW2021 – BT), be both robust and efficient, and limit unintended consequences. Towards this goal, system engineers strive to minimize technical debt and maximize the relevance of the needed capabilities for successful implementation of the system. If one was to follow the classical system engineering process, the system must meet certain needs. If there was a need for the system, be it perceived or an actual problem, the system engineering process, which is constantly evolving, must be enhanced to meet the needs of the 21st century. It is obvious that testing is necessary to validate that all the critical processes are functional and satisfy the system requirements allocated to software. However, there is a risk if the software is tested to a perceived operational environment based on theoretical workloads.